Effect of Different Salts on Nutrients Uptake, Gene Expression, Antioxidant, and Growth Pattern of Selected Rice Genotypes - Farooq, Muhammad; Asif, Saleem; Jang, Yoon-Hee; Park, Jae-Ryoung; Zhao, Dan-Dan; Kim, Eun-Gyeong; Kim, Kyung-Min (Frontiers in Plant Science, 2022)
Abstract: Climate change leads to soil salinization, and the dynamic scarcity of freshwater has negatively affected crop production worldwide, especially Oryza sativa. The association among ion uptake, gene expression, biomass, and root and shoot development under different salt stress is not fully understood. Many studies are related to the effect of NaCl only. This study used two salts (CaCl2 and MgCl2) along with NaCl and analyzed their effects on mineral uptake (macronutrients and micronutrients), gene expression, seed germination, plant growth, and biomass in different rice genotypes. CaCl2 (up to 200 mM) slightly increased the germination percentage and seedling growth, whereas 150 mM MgCl2 in the soil increased the root, shoot length, and fresh and dry weight in cultivars IR 28 and Cheongcheong. All agronomic traits among rice genotypes were drastically reduced by NaCl stress compared to other salts. Different salt stress differentially regulated ion uptake in the roots and shoots among different rice genotypes. Under different salt stress, a consistent decrease in Ca2+, Mn2+, and Fe2+ ions was observed in the roots of Cheongcheong, Nagdong, and IR 28. Similarly, under different salts, the stress in the shoots of Cheongcheong (Ca2+, Na+, and Zn2+) and Nagdong (Ca2+, Mg2+, Na+, and Zn2+) and the shoots of IR 28 (Ca2+ and Mg2+) consistently increased. Under different salts, a salt stress-related gene was expressed differentially in the roots of rice genotypes. However, after 6 and 12 h, there was consistent OsHKT1, OsNHX1, and OsSOS1 gene upregulation in the shoots of Nagdong and roots and shoots of the salt-tolerant cultivar Pokkali. Therefore, this study suggested that Pokkali responded well to NaCl stress only, whereas the plant molecular breeding lab cultivar Nagdong showed more salt tolerance to different salts (NaCl, CaCl2, and MgCl2). This can potentially be used by agriculturists to develop the new salt-tolerant cultivar “Nagdong”-like Pokkali.